How can we design better vaccines to prevent HIV infection in women? - Rafferty, Hannah; Sibeko, Sengeziwe; Rowland-Jones, Sarah (Frontiers in Microbiology, 2014)
The human immunodeficiency virus (HIV) burden in women continues to increase, and heterosexual contact is now the most common route of infection worldwide. Effective protection of women against HIV-1 infection may require a vaccine specifically targeting mucosal immune responses in the female genital tract (FGT). To achieve this goal, a much better understanding of the immunology of the FGT is needed. Here we review the architecture of the immune system of the FGT, recent studies of potential methods to achieve the goal of mucosal protection in women, including systemic-prime, mucosal-boost, FGT-tropic vectors and immune response altering adjuvants. Advances in other fields that enhance our understanding of female genital immune correlates and the interplay between hormonal and immunological systems may also help to achieve protection of women from HIV infection.